PERAN NON-STATE ACTORS DALAM GASTRODIPLOMACY INDONESIA MELALUI UBUD FOOD FESTIVAL - P.R.K.Dewi N.W.R.Priadarsini S (Jurnal Ilmiah Hospitality Management, 2018)
Gastrodiplomacy is present as an innovation of diplomacy practice through culinary that spreaded to various countries. As part of public diplomacy, it is considered more effective than diplomacy in general, so many countries now focus on strengthening gastrodiplomacy, including Indonesia. Indonesia which has variety of culinary as part of the culture also develop culinary as part of diplomacy. Enhancement of gastrodiplomacy is not only done overseas but also in the country, through the formal and informal sector conducted by state and non-state actors. Enhancement of gastrodiplomacy can be done through culinary festivals in the country like Ubud Food Festival (UFF). UFF is not only a culinary festival but also an event of preservation and promotion of Indonesian culinary heritage that can contribute to Indonesiaâ€™s tourism sector and economic growth. In UFF, non state actors play an important role in strengthening the Indonesian culinary. So in this paper, the authors analyze the role of non-state actors in the implementation of Indonesia's gastrodiplomacy program through the Ubud Food Festival. The research objectives are to know the non-state actors who play role in gastrodiplomacy Indonesia through UFF and analyze its role. The method used in conducting this research is descriptive qualitative research method. In this research, there are some non-state actors who play role in gastrodiplomacy such as non government, business or commerce group, civil society or citizen personal involvement, and mass media or information media. All of these non-state actors have actively played their roles and interrelated roles in enhancing Indonesia's culinary development through UFF. Through UFF, the internationalization of Indonesian culinary will be easier to do.Â Keywords: Public Diplomacy, Gastrodiplomacy, Non-State Actors, Ubud Food FestivalÂ